Implementasi Support Group Berbasis Resiliensi Dalam Meningkatkan Kualitas Hidup Lansia Hipertensi - Hariati Data; Friska Ernita Sitorus; Rostiodertina Girsang; Jekson Martiar Siahaan (Health Community Service, 2025)
Hypertension is one of the most prevalent chronic diseases among older adults and significantly affects their physical, psychological, and social well-being. Community-based psychosocial interventions are essential to improve self-management and quality of life among elderly individuals with hypertension. This community service program aimed to implement a resilience-based support group to enhance adaptive coping mechanisms and overall quality of life among elderly hypertensive patients. The program was conducted over six sessions involving health education, stress management training, peer sharing, spiritual reinforcement, and lifestyle modification guidance. Thirty-five elderly participants were involved. Evaluation was conducted using pre–post knowledge assessment and WHOQOL-BREF-based quality of life indicators. The results showed a 38% increase in hypertension-related knowledge, a 26% improvement in psychological well-being scores, and increased social engagement among participants. The resilience-based support group proved effective in strengthening emotional regulation, medication adherence, and social support. Integrating structured support groups into primary healthcare services is recommended to ensure sustainable community empowerment in elderly hypertension management.